Cantiones sacrae I (1589) - Byrd, William 1539/40-1623; Brown, Alan 1941-; Brett, Philip (London Stainer & Bell New York Galaxy Music Corp., 1988)
Byrd’s 1589 Cantiones Sacrae consists of 16 5-voice ‘sacred songs’, as the composer called them. They were probably composed over a number of years before the collection was assembled. Though serious in mood, they were intended as vocal chamber music for domestic performance. H.K. Andrews described them as ‘musically one of the great achievements of the century’.
Keywords: 16th Century (1501-1600); Song